Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T16:33:57+01:00
A) -4x + 20y + 6y + 3x = -x + 26y
b) 2x² + 4xy - 2x² - xy = 3xy
c) -xz + xy + xz - zy = xy - zy
d) 4x - 4y - 2x + 2y - 3x - 3xy = -x - 4y - 2y - 3xy
e) -10x + 5xy - 5xy - y - 10xy + 10x = -y - 10 xy
2009-12-07T16:34:33+01:00
Doprowadź wyrażenie do najprostszej postaci.
a) -4(x-5y)-3(-2y-x)
= -4x +20y +6y +3x =
= - x +26y

b) 2x(x+2y)-x(2x+y)=
= 2x² + 4xy -2x² -xy=
= 3xy

c) -x(z-y)-z(-x+y)=
= -xz +xy + xz -yz=
= xy -yz=
= y(x -z)

d) 4(x+y)-2(x-y)-3x(1+y)=
= 4x +4 y -2x +2y -3x -3xy=
= -x +6y -3xy

e) -5x(2-y)-y(5x+1)+10x(-y+1) =
= -10x + 5xy -5xy -y - 10xy +10x=
= -10xy - y =
= y(-10x -1)